AUTOARTERIAL PLASTY OF EXTERNAL CAROTID ARTERY IN CASE OF STENOSIS AND INTERNAL CAROTID ARTERY OCCLUSION - G. Yu. Sokurenko; A. V. Shatravka; A. V. Gusinskiy; S. A. Suvorov; M. R. Rizakhanova; I. A. Loginov (Вестник хирургии имени И.И. Грекова)
The research proved an efficacy of autoarterial plasty performance of external carotid artery in case of internal carotid artery occlusion. It isn’t necessary to apply synthetic materials or an autovein for closing arteriotomic defect in plasty performance. According to data of ultrasonic scintiangiography and transcranial Doppler graphy, there was noted the significant increase of blood flow on medial cerebral artery in operated area after a year of surgical treatment (about 30%). Proposed operation is effective in prevention plan of ischemic stroke.